Coupling Coordination and Spatiotemporal Dynamic Evolution Between Medical Services and Tourism Development in China - Xu, Shaogui; Zuo, Yifan; Law, Rob; Zhang, Mu; Han, Jiayu; Li, Gaopeng; Meng, Juewei (Frontiers in Public Health, 2022)
This paper constructs an evaluation index system and quantitatively explore the coupling coordination relationship between the tourism development system and the medical services system in China. Results show that during the period 2012-2019, the degree of coupling coordination between the tourism development system and medical services system showed a good upward trend in China. However, the relationship was barely balanced, with tourism development lagging. The overall layout shows a spatial pattern of “high in the north and low in the south, high in the east and low in the west.” The degree of coupling coordination tends to be randomly distribution from clustered distribution, and the cold-hot spots show a spatial development pattern of “cold in the northwest and hot in the southeast” as time goes on. Government regulation ability has always been an important mechanism affecting the degree of coupling coordination. The study aims to provide reference for the rationalization of medical tourism layout and sustainable development.